The principles for creation of fire-prevention forest belts with barriers of deciduous species for protection from crown fires - S. N. Sannikov; N. S. Sannikova; G. G. Terekhov (Сибирский лесной журнал, 2017)
The article discuss one of the priority security problems in Russia, which is elaboration of the strategic system of the forest and society safeguards from catastrophic forest crown fires in connection with rapid climate warming. It is postulated, that a most effective and reliable barrier for the dispersal of the intensive crown fire in a coniferous forest massive can be a sufficiently wide strip of deciduous tree species – «deciduous forest barrier», which has phytomass capable of absorbing crown fire energy and transforming them to surface fire, which may be extinguished by technical means. The actuality of the natural study of the transition parameters from the crown fire to surface fire has been noted, depending on climate, fire intensity and the deciduous barrier structure. The results of the quantitative natural investigation of the consequences of catastrophic crown fires of 2004 in the island pine forests of forest-steppe zone in Kurgan Oblast, which passed through the belt of 50–70 year-old birch stands of middle density, has been cited and formalized mathematically. It has been shown, that 150 m width of deciduous forest barrier is necessary as a minimum for the reliable transition of the high intensive front crown fire to surface fire in the forest-steppe conditions of the Western Siberia, but this width reduces with a decreasing heating effect. It has been proposed to create the complex fire-prevention forest belts of different construction for the protection of forests, industrial objects and settlements. Besides a basic deciduous barrier, their structure should include technologically necessary buffer zones and zones for the localization and extinguishing surface fire, which stop a crown fire. It has been recommended to use natural regeneration of deciduous tree species, as a most effective and non-deficient method for the creation of deciduous forest barriers in the predominant forest types, except the lichen pine forests, where creating deciduous belts is necessary.